Waqif preference of waqf-based qardhul hassan financing in Malaysia using a maqasid approach - Hanudin Amin; Faizah Panggi; Imran Mehboob Shaikh (Emerald Group Publishing Limited, 2024)
Purpose The purpose of this study is to develop a new framework to measure waqif preference of waqf-based qardhul hassan financing in Malaysia. Design/methodology/approach Using a maqāṣid approach, this study’s data were drawn from 286 valid usable questionnaires to examine the effects of consumer, family, ummah and humanity factors on the preference. Findings The study found that the said factors sourced from Attia’s maqāṣid al-Shariah were instrumental in determining waqif preference to donate in waqf-based qardhul hassan financing. Research limitations/implications Like others, this study’s findings are limited in terms of their generalisations and applications. The theory, context and variables used should be expanded in future works. Practical implications the results obtained are useful as a yardstick to enable the offered waqf-based qardhul hassan financing for improved mutual well-being among different classes of the wealth of societal groups in Malaysia. Furthermore, the results provide valuable insights into the direction for practitioners mainly managers involved in introducing waqf-based qardhul hassan financing as a new Islamic social financial instrument for poor and needy folks, at best. Originality/value This study is novel in terms of the proposed conceptual framework, where the waqif perspective comes into play.